Data from: Phenotypic and community consequences of captive propagation in mosquitofish - Wood, Zachary T.; Fryxell, David C.; Robinson, Rebecca R.; Palkovacs, Eric P.; Kinnison, Michael T. (Dryad, 2019)
1. Captive propagation can lead to phenotypic change in fish populations,
but the broader community-level consequences of captive phenotypes remain
largely unknown. 2. Here we investigate the degree to which captive
propagation alters the phenotypes and ecological roles of fish stocked
into wild communities. We focus on captive propagation of western
mosquitofish (Gambusia affinis) for biocontrol, which represents one of
the largest-scale production efforts for any fish released into the wild.
3. Captive propagation in mosquitofish consistently generated novel
mixtures of morphological and behavioral traits that deviate from those of
wild populations. 4. A mesocosm experiment showed that mosquitofish from
captive propagation facilities differ from wild fish in their effects on
aquatic community structure by shifting their consumption to less-mobile,
benthic prey. 5. Synthesis and applications: These findings provide
evidence that captive-propagated and translocated wild stocks not only
differ in phenotype, but can have substantially different ecological
effects on the communities into which they are introduced. Therefore,
captive propagation programs involving continual release should expand
their concerns beyond altered phenotypes and fitness to include whether
propagated fish actually provide the intended ecological roles and
services associated with wild counterparts. Infusions of wild alleles and
captive environments that mimic wild conditions are recommended strategies
to retain the desired ecological role of captive propagated fish
Morphology measurementsSee manuscript for fish source and measurement
detailsMorphology.csvExploration behavior trialsSee manuscript for trial
setupExploration_Behavior.csvMesocosm experiment dataSee manuscript for
mesocosm methods, including sample areas and
volumesMeso_Ecology.csvIn-mesocosm behavior observationsSee manuscript for
methods and variable descriptionsIn_Meso_Behavior.csv
Keywords: fish introductions; trophic cascades; captive-propagation; antipredator evolution